Highly air stable passivation of graphene based field effect devices1. Issue 8 (28th February 2015) - Sagade, Abhay A.; Neumaier, Daniel; Schall, Daniel; Otto, Martin; Pesquera, Amaia; Centeno, Alba; Elorza, Amaia Zurutuza; Kurz, Heinrich
<x xml:space="preserve">Abstract</x> As the GFETs are sensitive to surrounding environment and changes performance, proper passivation is required. Here usage of Al2O3 as an passivation layer is demonstrated with selection of proper seed layer.